Hubungan Antara Lingkungan Belajar dengan Semangat Belajar Anak Asuh di Panti Asuhan - Febrianty, Fawziah; Irmawita, Irmawita (Penerbit Aksara Rentaka Siar (ARS), 2019)
This research is in the background by the lack of enthusiasm for learning foster children in Panti Asuhan Tunas Bangsa, where an inadequate learning environment. This study aims to look at the relationship between the learning environment to foster the spirit of children’s learning in Panti Asuhan Tunas Bangsa Kelurahan Nan Balimo Kota Solok. This type of research is quantitative correlational research. The population in this study were all foster children in Panti Asuhan Tunas Bangsa Kelurahan Nan Balimo Kota Solok, with the number of population of 40 people. Data collection techniques questionnaire with data analysis and calculation of the precentace and product moment to see the connection. The results showed that there is a significant relationship between the learning environment to foster the spirit of children’s learning in Panti Asuhan Tunas Bangsa Kelurahan Nan Balimo Kota Solok.